Penerapan Konsep Bangunan Pintar Pada New Media Tower Universitas Multimedia Nusantara - Arianto Dwi Putro; Lutfi Prayogi (Program Sarjana Arsitektur Universitas Internasional Batam, 2021)
At this time the world has experienced extraordinary developments, one of which is in the technological aspect. The technology is currently very sophisticated, including in architecture. This is a competition in completing the complete building facilities. In order to achieve an energy-efficient and environmentally friendly building. Control systems and sensors in the form of technology can affect the building work system so that it can produce buildings that have advanced technology. The purpose of this research is to provide an insight into designing buildings with a smart building approach to produce buildings that are energy efficient, make it easier for building users, maintain building security, and are sustainable. The research method used is descriptive method. The object of this research was carried out in the building of educational facilities, namely Multimedia Nusantara University. Smart building is applied through several principles and consists of various aspects related to mechanical and electrical devices and security systems in buildings. All of these devices are controlled in a building automation system so that the building produces energy-efficient and environmentally friendly buildings. Smart buildings also have several architectural elements as elements that support the performance of the smart building system itself so that it can work optimally in realizing energy-efficient buildings.